Patterns in chlamydia detection rate in young adults aged 15–24 years in England, 2012–15: longitudinal analysis of routine data - Kim,S-H; Eaton,JW; Davies,B; Ward,H (2017)
BackgroundThe National Chlamydia Screening Programme (NCSP) in England recommends chlamydia testing for sexually active young adults (aged 15–24 years). The Public Health Outcomes Framework (PHOF) suggests that implementation and delivery of the NCSP should identify 2300 cases or more of chlamydia per 100000 residents (15–24 years old). The commissioning of chlamydia screening moved to local authorities in 2013. We describe performance of local authorities against the PHOF chlamydia screening recommendation.MethodsWe used chlamydia test data from Public Health England (2012–15), index of multiple deprivation (2015) data from National Office of Statistics, and population data to describe the association between the proportion of local authorities achieving the PHOF chlamydia detection rate recommendation and deprivation at local authority level, adjusted for population size and proportion of tests performed in a genitourinary medicine setting.FindingsThe number of chlamydia tests performed within the NCSP declined by 17% (1860000 in 2012 to 1538000 in 2015) over the study period. The proportion of local authorities that achieved the PHOF chlamydia diagnosis rate recommendation fell 39% (from 23% [75/324] in 2012 to 14% [45/324] in 2015). Throughout the 4-year period, local authorities in the most-deprived quintile were more likely to attain the recommendation than were local authorities in the least-deprived quintile (adjusted odds ratio 10·6 (95% CI 3·0–37·9) in 2012, 15·9 (2·0–129·5) in 2015).InterpretationThere has been a reduction in the number of chlamydia tests performed within the NCSP and a larger reduction in the proportion of local authorities meeting the chlamydia diagnosis rate recommendation since 2012. This finding suggests that the decline in testing may disproportionately affect those most at risk of chlamydia infection. There are also marked inequalities in attainment of the